Federalism and Consociationalism in Divided Societies: Comparative Evidence and Implications for Nepal's Federal Future - Basnet, Min Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: Federalism and consociationalism are two prominent institutional frameworks for managing diversity in divided societies. However, the relationship between them remains contested: does federalism require consociationalism to succeed, or can federalism function effectively without a formal power-sharing mechanism? Objective: This study critically examines the proposition that "federation cannot succeed without consociationalism" and assesses its relevance for Nepal's federal experiment, implemented since 2015. Methods: A qualitative comparative research design was employed, analysing secondary sources (journal articles, books, constitutional documents, policy reports). Successful federations (India, Germany, Switzerland, Belgium, Canada) and troubled federations (Nigeria, Ethiopia, Somalia, South Sudan) were compared against Nepal's ten-year federal experience. Results: Federalism alone is often insufficient to maintain political stability in deeply divided societies. Successful federations incorporate consociational practices – grand coalitions, proportionality, minority vetoes, segmental autonomy – either formally (Belgium, Switzerland) or informally (India). Troubled federations exhibit centralisation, exclusion, weak power-sharing, and corruption. Nepal's constitution includes inclusive norms but lacks robust consociational mechanisms, leading to implementation gaps, central dominance, and fragile institutions. Conclusion: In highly diverse societies, federalism requires consociational principles to function effectively. Nepal should institutionalise coalition governance, proportional representation (already partially present), minority protection mechanisms, and a cooperative political culture to stabilise its federal system. Implications for Policy: Strengthen intergovernmental councils, adopt formal grand-coalition requirements in the provinces, and ensure fiscal equity to prevent re-centralisation and minority disaffection.